Cyber Resilience Issues of Medical Cyber-Physical Systems - Alguliyev, Rasim; Aliguliyev, Ramiz; Sukhostat, Lyudmila (İnformasiya Texnologiyaları İnstitutu, 2025)
Medical cyber-physical system is a critical component of the medical device network. The application of cyber-physical systems in healthcare ranges from patient monitoring to various devices. Existing technologies in this area require constant updating and rapid response to ever-increasing cyberattacks. Among the most well-known threats to medical cyber-physical systems are tampering, phishing, spoofing, data exfiltration, ransomware, DoS, etc. Attackers try to disrupt the operation of medical cyber-physical systems and gain access to confidential medical data. Existing threats violate integrity, confidentiality, and availability. In this regard, various issues of medical cyberphysical systems' cyber resilience are considered in the paper.